ANALISIS PENGARUH PERPAJAKAN OLNINE, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Pada KPP Pratama Cabang Pulogadung) - Desy Amaliati Setiawan; Apry Linda Diana; Mochamad Yusuf (Bajang Institute, 2023)
This study aims to determine how much the relationship between online tax services, tax knowledge and taxpayer awareness of individual taxpayer compliance. This research uses associative or correlational research with a quantitative approach. This study used a sample of 50 respondents with a random sampling technique. The data used in this study are primary data with a questionnaire instrument. While testing the hypothesis in this study using multiple linear regression analysis and hypothesis testing using SPSS version 24.0. Based on the results of statistical calculations, it shows: (1) The relationship between variable X1 and variable Y has a positive and significant relationship with a value of significance t 0.000 <0.05. (2) The relationship of variable X2 to variable Y has a positive and significant relationship with a value of significance t 0.046 <0.05. (3) The relationship of variable X3 to variable Y has a positive and significant relationship with a significance value of t 0.000 <0.05. (4) The relationship of variables X1, X2, X3 to Y simultaneously has a positive and significant relationship. The conclusion is partially online tax service variables have a positive relationship to taxpayer compliance. Tax knowledge variable has a positive relationship with taxpayer compliance. Taxpayer awareness variable has a positive relationship with taxpayer compliance. And simultaneously online tax service variables, tax knowledge and taxpayer awareness have a positive relationship to taxpayer compliance